2019
DOI: 10.3389/fimmu.2018.03087
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Epigenetic Features of the Inactive X-Chromosome in NK Cells, Dendritic Cells, and Macrophages

Abstract: In females, the long non-coding RNA Xist drives X-chromosome Inactivation (XCI) to equalize X-linked gene dosage between sexes. Unlike other somatic cells, dynamic regulation of Xist RNA and heterochromatin marks on the inactive X (Xi) in female lymphocytes results in biallelic expression of some X-linked genes, including Tlr7, Cxcr3, and Cd40l, implicated in sex-biased autoimmune diseases. We now find that while Xist RNA is dispersed across the nucleus in NK cells and dendritic cells (DCs) and partially co-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
(46 reference statements)
1
30
1
Order By: Relevance
“…Interestingly, cells with TLR7 escape were also more efficient at class switch recombination during naïve B cell differentiation . Another study also reported that Tlr7 was biallelically expressed in a subset of murine female pDCs . In sum, recent findings support the hypothesis that dynamic XCI maintenance and immune cell specific XCI escape contributes to immune cell sexual dimorphism, and these mechanisms may be responsible for the female disposition toward autoimmunity.…”
Section: Escape From XCImentioning
confidence: 57%
See 3 more Smart Citations
“…Interestingly, cells with TLR7 escape were also more efficient at class switch recombination during naïve B cell differentiation . Another study also reported that Tlr7 was biallelically expressed in a subset of murine female pDCs . In sum, recent findings support the hypothesis that dynamic XCI maintenance and immune cell specific XCI escape contributes to immune cell sexual dimorphism, and these mechanisms may be responsible for the female disposition toward autoimmunity.…”
Section: Escape From XCImentioning
confidence: 57%
“…Indeed, we recently found evidence for diverse XCI maintenance in immune cells derived from both the lymphoid and myeloid lineages (Fig. ) . HSCs, common lymphoid progenitors (CLPs), and common myeloid progenitors (CMPs) have Xist RNA transcripts localized to the Xi, similar to fibroblasts .…”
Section: X‐chromosome Inactivation (Xci)mentioning
confidence: 96%
See 2 more Smart Citations
“…The four-core genotype mouse model is an elegant tool to study the effect of X/Y-linked genes, especially in gonadectomised mice. However, extrapolation of results from mouse models to humans is complicated as the regulation of XCI differs between mice and humans [50,51].…”
Section: Discussionmentioning
confidence: 99%